The socio-technical design of a SME knowledge community in the construction industry - Simões, Dora
This paper presents the socio-technical design of a knowledge community which is part of a system to support an industrial association based collaborative network in the sector of construction industry. There are many explanations around the virtual community concept. Here is presented a fundamental phase of the Know-Construct project which involved the design of the Construction Industry Knowledge (CIK) Community using three analytical approaches. The generic architecture of the supporting system (Knowledge Community Support - KCS) is described, highlighting information and knowledge management, community building facilities and semantic resources management.